A Bridge between Oncology Medicine and Eastern Orthodoxy - Cristina Pop (Journal of Religion & Society Supplement Series, 2026)
In this article, I draw from ethnographic research in an enclosed suspended bridge/passageway connecting a Romanian oncology hospital to an adjacent Eastern Orthodox church. I examine the space of the bridge as a “heterotopia of deviation,” that is, a real site where individuals are isolated, regulated, or contained. Even though it connects the oncology hospital and the church, the bridge itself is neither hospital nor church. First, the bridge functions temporarily as a place of festivity, especially during Sunday’s liturgical services. Second, the bridge is a space of transition and spatial and temporal liminality, where medical workers, patients, and their families can accommodate, disrupt, or resist the everyday practices of oncological care. Third, the bridge is a space of multiple juxtaposed orders, both secular and Orthodox. Methodologically, I highlight the value of participant observation in validating findings collected from other sources, such as interviews and literature review on Orthodoxy and oncologic care.